Fault-Tolerant Control for the Formation of Multiple Unknown Nonlinear Quadrotors via Reinforcement Learning⁎This work was supported by the National Natural Science Foundation of China under Grants 61873012, 61503012, and 61633007, and the Office of Naval Research under Grant N00014-17-1-2239. Issue 2 (2020) - Zhao, Wanbing; Liu, Hao; Lewis, Frank L.
Abstract: In this paper, the fault-tolerant control problem for the formation of unknown quadrotor team with nonlinearities, couplings, and actuator faults in the dynamics is investigated. A distributed observer is designed to estimate the position references for each quadrotor. A hierarchical control scheme is constructed including a fault-tolerant position controller to achieve the desired formation and a fault-tolerant attitude controller to track the attitude references. Reinforcement learning algorithms are designed to learn the optimal control policies of the position and attitude controllers. Simulation results are given to illustrate the effectiveness of the proposed controller.